2008
DOI: 10.1001/jama.299.9.1027
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nonpolypoid (Flat and Depressed) Colorectal Neoplasms in Asymptomatic and Symptomatic Adults

Abstract: Context Colorectal cancer is the second leading cause of cancer death in the United States. Prevention has focused on the detection and removal of polypoid neoplasms. Data are limited on the significance of nonpolypoid colorectal neoplasms (NP-CRNs). Objectives To determine the prevalence of NP-CRNs in a veterans hospital population and to characterize their association with colorectal cancer. Design, Setting, and Patients Cross-sectional study at a veterans hospital in California with 1819 patients undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
364
3
14

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 555 publications
(393 citation statements)
references
References 34 publications
(49 reference statements)
12
364
3
14
Order By: Relevance
“…Although the existence of these lesions had been reported earlier, their appreciable prevalence and potential significance in diagnosis and management of CRC attracted attention in the western literature during the development of the EU guidelines [58,59]. …”
Section: Discussionmentioning
confidence: 99%
“…Although the existence of these lesions had been reported earlier, their appreciable prevalence and potential significance in diagnosis and management of CRC attracted attention in the western literature during the development of the EU guidelines [58,59]. …”
Section: Discussionmentioning
confidence: 99%
“…These lesions, however, can protrude (or be recessed) significantly relative to the surrounding mucosa. 1,2 Conventional colonoscopy relying primarily on coloration is estimated to miss one out of every four lesions. 3,4 A method to provide endoscopic measurement of surface topography paired with conventional color imagery could reduce this high missed lesion rate.…”
Section: Introductionmentioning
confidence: 99%
“…However, white-light endoscopy alone is an imperfect technology that only offers structural details based on visual observation and can result in miss rates of up to 25% (16). It was also reported that flat lesions in the colon, which are more difficult to detect with white-light endoscopy, were fivefold more likely to contain cancerous tissue than the visually apparent polyps detected by conventional colonoscopy (17). This problem of failed detection could be significantly minimized with the addition of a molecular imaging component that reveals important functional information in conjunction with the structural component that white light endoscopes offer today.…”
mentioning
confidence: 99%